# if sk=13-5 Ky=2x+9 and SY=36-x find x

To solve the problem, we'll analyze the given equations step by step. You have three parts to the problem:
1. \( SK = 13 - 5 \)
2. \( KY = 2x + 9 \)
3. \( SY = 36 - x \)
First, let's simplify \( SK \):
\[
SK = 13 - 5 = 8
\]
Now we have:
1. \( SK = 8 \)
2. \( KY = 2x + 9 \)
3. \( SY = 36 - x \)
However, there is no direct information about the relationships between \( SK \), \( KY \), and \( SY \). Since we have values for \( SK \), let’s assume it could relate to \( KY \) and \( SY \) in some way, perhaps by thinking of a triangle where the sides are \( SK \), \( KY \), and \( SY \).
If we presume a relationship such as \( SK + KY = SY \):
\[
8 + (2x + 9) = (36 - x)
\]
Now, let's solve for \( x \):
\[
8 + 2x + 9 = 36 - x
\]
Combine the constants on the left side:
\[
17 + 2x = 36 - x
\]
Next, add \( x \) to both sides:
\[
17 + 3x = 36
\]
Subtract 17 from both sides:
\[
3x = 19
\]
Now, divide by 3:
\[
x = \frac{19}{3}
\]
Thus, the solution for \( x \) is:
\[
x = \frac{19}{3} \approx 6.33
\]
This value can be further verified by substituting back into previous expressions if necessary.